Comparing the Efficacies of Bisphosphonates’ Therapies for Osteoporosis Persistence and Compliance: A Systematic Review - Almohaileb, Faisal I.; Rasheed, Zafar (Current Molecular Medicine, 2022)
Objectives: Osteoporosis is the most prevalent metabolic bone disorder worldwide. This review was undertaken to compare the efficacies of bisphosphonates therapies for patient persistence and compliance for the treatment of osteoporosis. Methods: A systematic review was performed in accordance with the available reporting items. MEDLINE and Cochrane library databases were applied for literature searched up to January 2020. All major studies such as prospective, retrospective and review articles that examined patient persistence or compliance to bisphosphonates for osteoporosis were included. Results: The literature search found 656 relevant published reports, out of which 87 were included. The 10, 712, 176 osteoporotic patients were studied for patient persistence and 5, 875, 718 patients were studied for patient compliances. Analysis of all studied bisphosphonates showed almost similar patterns for patient persistence rates as it was decreased over the time following initial prescription, but persistence length was found to be significantly higher for alendronate therapy as compared to the other studied bisphosphonates (p<0.001), whereas the length of persistence of all other bisphosphonates (other than alendronate) were almost same (p>0.05). Analysis of patient compliances with etidronate therapy showed the highest percent medication possession ratio (MRP) at 12 months, followed by the MRPs of ibandronate, alendronate, risedronate, and clodronate. Conclusion: This is the first systematic review that shows the comparison of the efficiencies of bisphosphonates for patient persistence and compliance for the treatment of osteoporosis. The data showed that the length of patient persistence was highest for alendronate therapy, whereas patient compliance was highest for etidronate therapy for the treatment of osteoporosis.
Keywords: compliances